Accelerated appearance-only SLAM - Cummins, M; Newman, P; IEEE (2008)
This paper describes a probabilistic bail-out condition for multihypothesis testing based on Bennett's inequality. We investigate the use of the test for increasing the speed of an appearance-only SLAM system where locations are recognised on the basis of their sensory appearance. The bail-out condition yields speed increases between 25x-50x on real data, with only slight degradation in accuracy. We demonstrate the system performing real-time loop closure detection on a mobile robot over multiple-kilometre paths in initially unknown outdoor environments. ©2008 IEEE.